Impact dynamics of porcine drip bloodstains on fabrics. (May 2016) - Williams, Elisabeth M.P.; Dodds, Margaret; Taylor, Michael C.; Li, Jingyao; Michielsen, Stephen
Graphical abstract: Highlights: Blood impact dynamics on surfaces divide into two regimes, t  < 30 and t  ≥ 30 ms. Drip stains exhibit similar behavior on paper, woven and knit fabrics for t  < 30 ms. For t  ≥ 30 ms, blood wicks into fabrics, expanding stain area and distorting shapes. The number of satellite stains observed was much higher on fabrics than on paper. Abstract: As a passive blood drop impacts a hard surface, it is observed to collapse and spread laterally, then retract and settle. During the spreading phase, the edge of the drop may rise forming a crown extending into spines and breaking up into secondary drops. When a similar drop falls onto a textile surface these same processes may occur, but the process of blood wicking into the fabric complicates stain formation. These processes are described within for passive drip stains collected under controlled conditions using anticoagulated porcine blood. Three stages of this impact process were identified and could be separated into distinct time zones: (1) spreading (time t  ≤ 2.5 ms) and (2) retraction (2.5 ≤  t  ≤ 12 ms) on the surface with potential splashing at the periphery, and (3) wicking (30 ms ≤  t  ≤ 30 min) of the blood into the fabric. Although wetting and wicking may also occur for t  < 30 ms, the vast majority of wetting and wicking occur after this time and thus the short-time wicking can be ignored. In addition, the number of satellite stains correlates with the surface roughness with the number of satellites for jersey knit > plain-woven > cardboard. Conversely, the size of the satellite stains correlates with the amount of wicking in the fabric with the satellite stain size for plain-woven > jersey knit > cardboard.